2005
DOI: 10.1111/j.1471-6402.2005.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Yoga, Body Awareness, and Body Responsiveness to Self-Objectification and Disordered Eating

Abstract: Study 1 tested whether yoga practice is associated with greater awareness of and responsiveness to bodily sensations, lower self‐objectification, greater body satisfaction, and fewer disordered eating attitudes. Three samples of women (43 yoga, 45 aerobic, and 51 nonyoga/nonaerobic practitioners) completed questionnaire measures. As predicted, yoga practitioners reported more favorably on all measures. Body responsiveness, and, to some extent, body awareness significantly explained group differences in self‐ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
289
1
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(324 citation statements)
references
References 53 publications
(93 reference statements)
21
289
1
13
Order By: Relevance
“…Elképzelésünk szerint a nagyobb fokú testi tudatosság együtt jár a pozitív affektivitás magasabb szintjével (ami a pszichológiai jóllét egy mutatójának is tekinthetô), ugyanakkor független a negatív affektivitástól. A mérôeszköz kritériumvaliditását egy rendszeresen jógázó minta bevonásával vizsgáltuk, mivel a jógagyakorlás egyik deklarált céljának a testi folyamatokra irányuló figyelem fejlesztése számít, s empirikus eredmények szerint a testi tudatosság szintje jógázók körében valóban magasabb (Daubenmier, 2005;Mehling és mtsai, 2009; Tihanyi, Sági, Csala, Tolnai, & Köteles, megjelenés alatt).…”
Section: Testi Tudatosság -Definíció éS Jelentôségunclassified
“…Elképzelésünk szerint a nagyobb fokú testi tudatosság együtt jár a pozitív affektivitás magasabb szintjével (ami a pszichológiai jóllét egy mutatójának is tekinthetô), ugyanakkor független a negatív affektivitástól. A mérôeszköz kritériumvaliditását egy rendszeresen jógázó minta bevonásával vizsgáltuk, mivel a jógagyakorlás egyik deklarált céljának a testi folyamatokra irányuló figyelem fejlesztése számít, s empirikus eredmények szerint a testi tudatosság szintje jógázók körében valóban magasabb (Daubenmier, 2005;Mehling és mtsai, 2009; Tihanyi, Sági, Csala, Tolnai, & Köteles, megjelenés alatt).…”
Section: Testi Tudatosság -Definíció éS Jelentôségunclassified
“…One possible candidate might be body awareness (i.e. 'perception of bodily states, processes and actions that is presumed to originate from sensory proprioceptive and interoceptive afferents and that an individual has the capacity to be aware of ';mehLing et al 2009, 4), which was found to be connected to psychological well-being in several empirical studies (dauBenmier 2005;köTeLes 2014;tiHanyi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Sacha and Russ (2006) as well as Mainwaring and Krasnow's (2010) studies are in line with Daubenmier's (2005) study of the relationships between movement activities and body awareness, which concluded that body awareness seems to predispose enjoyment and to be beneficial to expertise development in movement performance activities. The studies above (Mainwaring & Krasnow, 2010;Nordin & Cumming, 2005), identified that imagery is important in developing a sense of enjoyment.…”
Section: Master Teachers As Role Modelssupporting
confidence: 67%